1,2,4-Triazolo[1,5-a]pyrimidines as a Novel Class of Inhibitors of the HIV-1 Reverse Transcriptase-Associated Ribonuclease H Activity - Jenny Desantis (Molecules, 2020)
Despite great efforts have been made in the prevention and therapy of human immunodeficiency virus (HIV-1) infection, however the difficulty to eradicate latent viral reservoirs together with the emergence of multi-drug-resistant strains require the search for innovative agents, possibly exploiting novel mechanisms of action. In this context, the HIV-1 reverse transcriptase (RT)-associated ribonuclease H (RNase H), which is one of the few HIV-1 encoded enzymatic function still not targeted by any current drug, can be considered as an appealing target. In this work, we repurposed in-house anti-influenza derivatives based on the 1,2,4-triazolo[1,5-a]-pyrimidine (TZP) scaffold for their ability to inhibit HIV-1 RNase H function. Based on the results, a successive multi-step structural exploration around the TZP core was performed leading to identify catechol derivatives that inhibited RNase H in the low micromolar range without showing RT-associated polymerase inhibitory activity. The antiviral evaluation of the compounds in the MT4 cells showed any activity against HIV-1 (IIIB strain). Molecular modelling and mutagenesis analysis suggested key interactions with an unexplored allosteric site providing insights for the future optimization of this class of RNase H inhibitors.